Penerapan Sistem Manajemen Iso 9001:2015 Pada Proyek Pembangunan Gedung Parkir Mall Panakkukang - Hendrika Benyamin; Helen Adry Irene Sopacua; Herby Calvin Pascal Tiyouw (Universitas Kristen Indonesia Paulus, 2025)
This study examines the implementation of ISO 9001:2015 in quality management for the construction project of the Panakkukang Mall parking building. The primary objective of this research is to evaluate the effectiveness of applying this quality management standard in enhancing project quality and customer satisfaction. The method used is a descriptive approach, with data collected through observation, interviews, and documentation. The findings indicate that the implementation of ISO 9001:2015 significantly contributes to improvements in managerial processes, quality control, and communication among all parties involved in the project. The involvement of all team members in applying this standard has also proven to enhance their understanding, awareness of responsibilities, and the quality of their work. However, challenges remain in implementation, such as staff training and the provision of adequate resources. This study aims to provide recommendations to developers and contractors to further optimize the application of quality management systems for achieving better outcomes in future construction projects.